2004
DOI: 10.1038/sj.bjp.0705669
|View full text |Cite
|
Sign up to set email alerts
|

The role of bradykinin, AT2 and angiotensin 1–7 receptors in the EDRF‐dependent vasodilator effect of angiotensin II on the isolated mesenteric vascular bed of the rat

Abstract: 1 The mechanisms involved in the vasodilator actions of angiotensin II (Ang II) have not yet been completely elucidated. We investigated the potential mechanisms that seem to be involved in the Ang II vasodilator effect using rat isolated mesenteric vascular bed (MVB). 2 Under basal conditions, Ang II does not affect the perfusion pressure of MVB. However, in vessels precontracted with norepinephrine, Ang II induces vasodilation followed by vasoconstriction. Vasoconstrictor, but not the vasodilation of Ang II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The role of K + channels in angiotensin II-mediated vasorelaxation has been already described (10,21). Our results have shown that apamin, a selective blocker of the low-conductance Ca…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The role of K + channels in angiotensin II-mediated vasorelaxation has been already described (10,21). Our results have shown that apamin, a selective blocker of the low-conductance Ca…”
Section: Discussionsupporting
confidence: 73%
“…Thus, we may suggest that SK Ca , K ir , and K ATP channels most probably do not participate in RRA response to angiotensin II. In accordance to this finding, Dimitroupoulou et al (11) and De Moura et al (21) found that activation of SK Ca , K ir , and K ATP are not involved in the angiotensin IIinduced rat mesenteric artery relaxation. On the other hand, we have shown that administration of TEA or charybdotoxin (a blocker of large-conductance Ca 2+ -activated K + channels) produced significant but not complete inhibition of angiotensin II-induced relaxation.…”
Section: +mentioning
confidence: 63%
“…Angiotensin II has been shown previously to stimulate exaggerated apoptosis in a variety of cells [32][33][34][35], including endothelial cells, which possess receptors to angiotensin II on their membranes [36,37]. For the HUVEC cell line, the protocols for angiotensin IIinduced apoptosis are usually based on at least 18 h incubation [38,39], which was not the case in our experimental set-up.…”
Section: Discussionmentioning
confidence: 93%
“…Weak vasodilator actions of Ang-(1–7) given systemically contrasts with the more pronounced effects of the peptide when administered to isolated blood vessels (Almeida et al, 2000; Brosnihan et al, 1996, 1998; Fernandes et al, 2001; Gorelik et al, 1998; Kozlovski et al, 2007; Machado et al, 2002; Meng & Busija, 1993; Neves et al, 2004; Oliveira et al, 1999; Osei et al, 1993; Sampaio et al, 2007; Soares de et al, 2004; Tirapelli et al, 2006), a finding that underscores a paracrine rather than a systemic effect of this angiotensin peptide. There is agreement that Ang(1–7) vasodilator responses are in part related to release of bradykinin and endothelium-derived nitric oxide as well as a direct effect of Ang-(1–7) on the mas-R (Almeida et al, 2000; Brosnihan et al, 1996, 1998; Davie & McMurray, 1999; Fernandes et al, 2001; Gorelik et al, 1998; Heitsch et al, 2001; Kozlovski et al, 2007; Lemos et al, 2005; Li et al, 1997a; Li et al, 1997b: Marangoni et al, 2006; Oliveira et al, 1999, 2002, 2003; Sampaio et al, 2007; Soares de et al, 2004; Tirapelli et al, 2006).…”
Section: The Ace2/ang-(1–7)/mas Axismentioning
confidence: 98%